Micrometeorological impacts of offshore wind farms as seen in observations and simulations. (29th November 2018) - Siedersleben, S K; Lundquist, J K; Platis, A; Bange, J; Bärfuss, K; Lampert, A; Cañadillas, B; Neumann, T; Emeis, S
Abstract: In Europe, offshore wind farms have a capacity of 16 GW, with 71% installed at the North Sea. These wind farms represent an additional source of turbulence and may influence the stratification of the marine boundary layer. We present aircraft measurements and simulations showing an impact on temperature and humidity at hub height in the order of 0.5 K and 0.5 g kg −1 even 60 km downwind of a wind farm cluster. We extend these simulations to explore a realistic future scenario, suggesting wakes in potential temperature and water vapor propagating more than 100 km downwind. Such impacts of wind farms are only observed in case of a strong stable stratification at rotor height, allowing wind farms to mix warmer air downward.